Causal associations between dietary factors and colorectal cancer risk: a Mendelian randomization study - Zhang, Xu; Wu, Zhimeng; Wang, Xiangrui; Xin, Binglong; Hu, Ping; Yin, Yan; He, Shuixiang; Ren, Mudan (Frontiers in Nutrition, 2024)
Background: Previous epidemiological studies have found a link between colorectal cancer (CRC) and human Dietary habits. However, the inherent limitations and inevitable confounding factors of the observational studies may lead to the inaccurate and doubtful results. The causality of Dietary factors to CRC remains elusive. Methods: We conducted two-sample Mendelian Randomization (MR) analyses utilizing the data sets from the IEU Open GWAS project. The exposure datasets included Alcoholic drinks per week, Processed meat intake, Beef intake, Poultry intake, Oily fish intake, Non-oily fish intake, Lamb/mutton intake, Pork intake, Cheese intake, Bread intake, Tea intake, Coffee intake, Cooked vegetable intake, Cereal intake, Fresh fruit intake, Salad/raw vegetable intake, and Dried fruit intake. In our MR analyses, the Inverse variance weighted (IVW) method was employed as the primary analytical approach. The weighted median, MR-Egger, weighted mode, and simple mode were also applied to quality control. Heterogeneity and pleiotropic analyses were implemented to replenish the accuracy of the results. Results: MR consequences revealed that Alcoholic drinks per week (odds ratio (OR): 1.565, 95% confidence interval (CI): 1.068-2.293, p = 0.022), Non-oily fish intake (OR: 0.286; 95% CI: 0.095-0.860; p = 0.026), Fresh fruit intake (OR: 0.513; 95% CI: 0.273-0.964; p = 0.038), Cereal intake (OR: 0.435; 95% CI: 0.253-0.476; p = 0.003) and Dried fruit intake (OR: 0.522; 95% CI: 0.311-0.875; p = 0.014) was causally correlated with the risk of CRC. No other significant relationships were obtained. The sensitivity analyses proposed the absence of heterogeneity or pleiotropy, demonstrating the reliability of the MR results. Conclusions: This study indicated that Alcoholic drinks were associated with an increased risk of CRC, while Non-oily fish intake, Fresh fruit intake, Cereal intake, and Dried fruit were associated with a decreased risk of CRC. This study also indicated that other Dietary factors included in this research were not associated with CRC. The current study is the first to establish the link between comprehensive Diet-related factors and CRC at the genetic level, offering novel clues for interpreting the genetic etiology of CRC and replenishing new perspectives for the clinical practice of gastrointestinal disease prevention..